EVALUATING THE ECONOMIC IMPLICATIONS OF INTERNATIONAL MONETARY FUND (IMF) PROGRAMS ON PAKISTAN: A DECADE-LONG ANALYSIS (2014-2024) - Asad Ullah; Salman Khan; Dr. Jamal Ud Din (International Journal of Contemporary Issues in Social Sciences, 2024)
This research paper evaluates the economic implications of International Monetary Fund (IMF) programs on Pakistan from 2014 to 2024. Since its first engagement with the IMF in 1958, Pakistan has entered into numerous agreements that have profoundly shaped its economic trajectory. Through a detailed case study approach, historical analysis, and qualitative assessments, this study aims to critically assess the decade-long impact of IMF programs on Pakistan’s economy. It explores how IMF-mandated reforms, tied to loan agreements, have affected key sectors such as education and healthcare, influenced fiscal policy decisions, and impacted Pakistan’s economic sovereignty. By examining this complex relationship, the research seeks to provide a nuanced understanding of the IMF's role in shaping Pakistan’s economic landscape over the last decade.